The Irradiance Optimation for Growing Spirulina fusiformis: Biomass, Phycocyanin, and Protein Production - Awalina Satya; Tjandra Chrismadha; Ika Atman Satya (Indonesian Society of Limnology, 2021)
The optimization of cyanobacterium microalgae cultivation technology to provide the need for food or feedstocks has recently attracted many investigators. An optimum operation on microalgae cultivation is important to reduce the excessive workload on the aquatic environment. Therefore, this study describes how the varied irradiance (2000 lux, 4000 lux, 6000 lux, 8000 lux, and 10,000 lux) treatments on a bubble column photobioreactor system affected biomass production, phycocyanin, and protein from cyanobacterium Spirulina fusiformis. The objective of this study was to obtain the optimum irradiance for producing maximum biomass, phycocyanin, and protein simultaneously. The results demonstrated some findings those were: 1) irradiance 10,000 lux made doubling time of growth earliest (only 24 hours) while 2,000 lux doubled within five days later; 2) light response curve showed that the increase of biomass concentration was linear with the increasing of irradiance; 3) a predictive model (Response Surface Method) proof that the most optimum quantity of the biomass (0.58 ±0.035 gL-1 dry weight), chlorophyll-a (0.090 ±0.023 % dry weight), and phycocyanin (2.44 ±0.00 gL-1 dry weight) were obtained on 10,000 lux, while protein contents of 79.18±5.47 % dry weight attained on the irradiance of 6000 lux. The maximum productivity of the biomass, chlorophyll-a, phycocyanin, and protein was Pbiomass of 24.95 mgL-1day-1; Pchl-a of 2.25E-02 mgL-1day-1; Pphycocyanin of 1.88E-02 mgL-1day-1; and Pprotein of 17.56 mgL-1day-1. Enhancement of irradiance up to 5 folds lead to the increasing of biomass chlorophyll-a, phycocyanin, and protein productivity, attained to 1.7, 5.01, 4.13, and 2.81 folds, respectively. The irradiance had a significant influence on the production of the metabolites; therefore, the irradiance must be optimized.